Analyzing the enhancement of production efficiency using FMEA through simulation-based optimization technique: A case study in apparel manufacturing. Issue 1 (1st January 2017) - Pazireh, E.; Sadeghi, A.H.; Shokohyar, S.
Abstract: In service and production area, problems such as severity of competition and increasing customers' expectations, put the producers' under a commitment to eliminate product defects and make up for any kind of shortage and deviations in its performance. In order to reach the mentioned aim, failure mode and effects analysis (FMEA) technique can be typically utilized for prevention, identification, control and elimination of possible errors. In this paper, FMEA approach is adopted to design and implement a system of quality control in the apparel production lines, to identify and rank the possible difficulties, and then finally, to issue the right commands to the quality control stations. For this purpose, the data are gathered from a medium-sized apparel factory and implemented by FMEA and then, improvability of production efficiency is analyzed using simulation-based optimization technique. The results of the simulation show significant decrease in product defects, rework, and total production cost.